Japanese Wartime Zoo Policy - Itoh, M. author. aut Link
XX, 245 p. 4 illus.
Keywords: This book examines Japanese wartime zoo policy during World War II, analyzing the reasons why the Home Ministry destroyed more than 300 showpiece animals throughout Japan well before U.S. air strikes were anticipated, with international comparisons of the effects of the war on zoos in Europe, the United States, and the Middle East.